Persistence of immune response in heterologous COVID vaccination schedules in the Com-COV2 study - a single-blind, randomised trial incorporating mRNA, viral-vector and protein-adjuvant vaccines - Shaw, RH; Greenland, M; Stuart, AS; Aley, PK; Andrews, NJ; Cameron, JC; Charlton, S; Clutterbuck, EA; Collins, AM; Darton, T; Dinesh, T; Duncan, CJ; et al. (Elsevier, 2023)
Background Heterologous COVID vaccine priming schedules are immunogenic and effective. This report aims to understand the persistence of immune response to the viral vectored, mRNA and protein-based COVID-19 vaccine platforms used in homologous and heterologous priming combinations, which will inform the choice of vaccine platform in future vaccine development. Methods Com-COV2 was a single-blinded trial in which adults ≥ 50 years, previously immunised with single dose ‘ChAd’ (ChAdOx1 nCoV-19, AZD1222, Vaxzevria, Astrazeneca) or ‘BNT’ (BNT162b2, tozinameran, Comirnaty, Pfizer/BioNTech), were randomised 1:1:1 to receive a second dose 8–12 weeks later with either the homologous vaccine, or ‘Mod’ (mRNA-1273, Spikevax, Moderna) or ‘NVX’ (NVX-CoV2373, Nuvaxovid, Novavax). Immunological follow-up and the secondary objective of safety monitoring were performed over nine months. Analyses of antibody and cellular assays were performed on an intention-to-treat population without evidence of COVID-19 infection at baseline or for the trial duration. Findings In April/May 2021, 1072 participants were enrolled at a median of 9.4 weeks after receipt of a single dose of ChAd (N = 540, 45% female) or BNT (N = 532, 39% female) as part of the national vaccination programme. In ChAd-primed participants, ChAd/Mod had the highest anti-spike IgG from day 28 through to 6 months, although the heterologous vs homologous geometric mean ratio (GMR) dropped from 9.7 (95% CI (confidence interval): 8.2, 11.5) at D28 to 6.2 (95% CI: 5.0, 7.7) at D196. The heterologous/homologous GMR for ChAd/NVX similarly dropped from 3.0 (95% CI:2.5,3.5) to 2.4 (95% CI:1.9, 3.0). In BNT-primed participants, decay was similar between heterologous and homologous schedules with BNT/Mod inducing the highest anti-spike IgG for the duration of follow-up. The adjusted GMR (aGMR) for BNT/Mod compared with BNT/BNT increased from 1.36 (95% CI: 1.17, 1.58) at D28 to 1.52 (95% CI: 1.21, 1.90) at D196, whilst for BNT/NVX this aGMR was 0.55 (95% CI: 0.47, 0.64) at day 28 and 0.62 (95% CI: 0.49, 0.78) at day 196. Heterologous ChAd-primed schedules produced and maintained the largest T-cell responses until D196. Immunisation with BNT/NVX generated a qualitatively different antibody response to BNT/BNT, with the total IgG significantly lower than BNT/BNT during all follow-up time points, but similar levels of neutralising antibodies. Interpretation Heterologous ChAd-primed schedules remain more immunogenic over time in comparison to ChAd/ChAd. BNT-primed schedules with a second dose of either mRNA vaccine also remain more immunogenic over time in comparison to BNT/NVX. The emerging data on mixed schedules using the novel vaccine platforms deployed in the COVID-19 pandemic, suggest that heterologous priming schedules might be considered as a viable option sooner in future pandemics. ISRCTN:27841311 EudraCT:2021-001275-16.